Strategi Pengembangan Bisnis Sapi Pedaging Kelompok Ternak Berkah Usaha di Blora - Ilham Dzikri Fajrianto; Suprehatin Suprehatin (Forum Agribisnis, 2020)
Farmer's group Berkah usaha at the beginning originally had two types of livestock businesses which are cattle and sheep. However, Berkah Usaha is focusing on cattle only. The development of the cattle business in this group is important to fulfil the increasing national demand for beef each year. This development of cattle business is also in line with the program of the local government of Blora which is making this district as a centre of cattle farm production. This study aims to formulate the cattle business development strategy for Berkah Usaha group by identifying the main internal and external factors. The study used four key informants as a respondent to identify the group's business environment and formulate business strategies. The analytical method used are IFE, EFE, IE, and SWOT matrix. The results showed that the Berkah Usaha's main internal key factors are cattle feed business and qualified cattle breeds while the main external key factors are government policies and climate variability. The results of this study also showed that there are six alternative business development strategies such as collaboration to develop regional livestock cluster and procurement of good cattle breeds.